2022
DOI: 10.3390/ani12213015
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Extramedullary Plasmacytoma in Dogs and a Cat: Clinical Characteristics and Histopathological Findings

Abstract: Background: Extramedullary plasmacytoma (EMP) is a plasma cell tumor that is very rarely reported in ocular and adnexal tissue and is usually solitary and benign. Methods: This study evaluated seven cases from different ophthalmology referrals submitted for histopathological analysis between 2013 and 2022. Results: EMPs were diagnosed in a 9-year-old domestic short-haired cat and in six dogs (median age, 10 years): three English Cocker Spaniels, a Golden Retriever, a Maltese, and a Pinscher. EMPs affected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…One study found the most frequent site of origin to be the skin [ 5 ], whilst other reports suggested oral plasmacytomas are the most common [ 1 , 2 , 3 ]. The incidence of plasmacytomas in cats is much lower, and the literature mostly consists of case reports of a single animal [ 7 , 8 , 9 , 10 , 11 ], although there are some studies with larger sample numbers ( n = 7–11) [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found the most frequent site of origin to be the skin [ 5 ], whilst other reports suggested oral plasmacytomas are the most common [ 1 , 2 , 3 ]. The incidence of plasmacytomas in cats is much lower, and the literature mostly consists of case reports of a single animal [ 7 , 8 , 9 , 10 , 11 ], although there are some studies with larger sample numbers ( n = 7–11) [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%